Basil Wilson Duke, CSA : the right man in the right place - Matthews, Gary Robert, 1949- (University Press of Kentucky, 2005)
After practicing law for several years in St. Louis, Basil Wilson Duke (1838-1916) enlisted in the Confederate army in 1861 and was elected first lieutenant of John Hunt Morgan's legendary cavalry unit. As second in command, he was, Morgan recorded, "wise in counsel, gallant in the field," and always "the right man in the right place." Duke was twice wounded in battle and was captured during Morgan's Great Raid and held prisoner for over a year. When Morgan, who was also Duke's brother-in-law, was killed in 1864, Duke was promoted to brigadier general and appointed commander of Morgan's men. M.